2022
DOI: 10.1002/adma.202207107
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Extracellular Vesicles with SHP2 High Expression Promote Mitophagy for Alzheimer's Disease Treatment

Abstract: Mitochondrial dysfunction is a fundamental pathological feature of Alzheimer's disease (AD). However, toxicity and poor brain enrichment of existing mitophagy inducers limit their further applications. In this study, a platform for AD therapy is developed using nanosized mesenchymal‐stem‐cells‐derived extracellular vesicles with tyrosine phosphatase‐2 (SHP2) high‐expression (MSC‐EVs‐SHP2). The high blood–brain barrier penetration ability of MSC‐EVs‐SHP2 is demonstrated in AD‐mice, facilitating SHP2 delivery to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 47 publications
1
38
0
Order By: Relevance
“…Thus, INH administration of MSC-EVs-carrying miRNAs might provide a good reference. More importantly, we found that miR-146a-5p-EVs were generally more potent than Hypo-EVs in suppressing airway inflammation and remodeling in asthmatic mice, which further supported the notion that engineering MSC-EVs is an effective way to improve the therapeutic effect of MSC-EVs ( 45 , 46 ).…”
Section: Discussionsupporting
confidence: 80%
“…Thus, INH administration of MSC-EVs-carrying miRNAs might provide a good reference. More importantly, we found that miR-146a-5p-EVs were generally more potent than Hypo-EVs in suppressing airway inflammation and remodeling in asthmatic mice, which further supported the notion that engineering MSC-EVs is an effective way to improve the therapeutic effect of MSC-EVs ( 45 , 46 ).…”
Section: Discussionsupporting
confidence: 80%
“…Proteins as important regulator molecules, play a critical role in various disease therapies. A growing number of studies show that genetically engineered MSC-EVs containing therapeutic proteins were used in disease treatments [160][161][162]. For example, in the context of AD, Xu F et al infected MSCs with lentivirus encoding the Src homology 2 domaincontaining protein tyrosine phosphatase-2 (SHP2) gene to obtain MSC-EVs with high level of SHP2 [162].…”
Section: Drug-loaded Msc-evs For Ad Therapymentioning
confidence: 99%
“…A growing number of studies show that genetically engineered MSC-EVs containing therapeutic proteins were used in disease treatments [160][161][162]. For example, in the context of AD, Xu F et al infected MSCs with lentivirus encoding the Src homology 2 domaincontaining protein tyrosine phosphatase-2 (SHP2) gene to obtain MSC-EVs with high level of SHP2 [162]. As a result, mitophagy is significantly induced by MSC-EVs-SHP2, which ameliorates mitochondrial damage-mediated apoptosis and NLRP3 activation in neuronal cells.…”
Section: Drug-loaded Msc-evs For Ad Therapymentioning
confidence: 99%
“…393 Due to their biological origin, they offer several advantages over traditional synthetic nanoparticles, including lower immunogenicity, enhanced stability, improved safety, and better cellular uptake, which have shown promising results in preclinical studies for cancer therapy. 394,395 Among cell-derived nanomaterials, cell membrane-encapsulated nanoparticles possess potential immune-evasive properties and prolonged circulation times in vivo. 396 Given this, He et al utilized red blood cell coated nanoparticles to codeliver antiapoptotic protein inhibitor ABT-263 (ABT) and A-1210477 (A12) for GBM.…”
Section: Liposome-based Nanomaterials For Targetingmentioning
confidence: 99%
“…Bionic nanomaterials like membrane-coated nanoparticles and extracellular vesicles show great potential in biomedical use due to their easy production, excellent biocompatibility, and ability to target tumors and evade the immune system . Due to their biological origin, they offer several advantages over traditional synthetic nanoparticles, including lower immunogenicity, enhanced stability, improved safety, and better cellular uptake, which have shown promising results in preclinical studies for cancer therapy. , …”
Section: Nanodelivery Systems For Sniping Cscsmentioning
confidence: 99%